2018
DOI: 10.1101/397653
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FACT and Ubp10 collaborate to modulate H2B deubiquitination and nucleosome dynamics

Abstract: Monoubiquitination of histone H2B (H2B-Ub) plays a role in transcription and DNA replication, and is required for normal localization of the histone chaperone, FACT.In yeast, H2B-Ub is deubiquitinated by Ubp8, a subunit of SAGA, and Ubp10. Although they target the same substrate, loss of Ubp8 and Ubp10 causes different phenotypes and alters the transcription of different genes. We show that Ubp10 has poor activity on yeast nucleosomes, but that addition of FACT stimulates Ubp10 activity on nucleosomes and not … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 95 publications
3
11
0
Order By: Relevance
“…In addition to the roles of FACT described in yeast, we showed that FACT repressed cryptic transcription through Usp7 by regulating H2Bub in mouse ESCs. Consistently, it was recently found that FACT mutant yeast demonstrated an increased level of H2Bub ( 78 ). The depletion of Ubp10, yeast counterpart of H2Bub deubiquitinase Usp7, activates cryptic transcription reporter in yeast strains with weak FACT mutation ( spt16–11 ) ( 78 ).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In addition to the roles of FACT described in yeast, we showed that FACT repressed cryptic transcription through Usp7 by regulating H2Bub in mouse ESCs. Consistently, it was recently found that FACT mutant yeast demonstrated an increased level of H2Bub ( 78 ). The depletion of Ubp10, yeast counterpart of H2Bub deubiquitinase Usp7, activates cryptic transcription reporter in yeast strains with weak FACT mutation ( spt16–11 ) ( 78 ).…”
Section: Discussionsupporting
confidence: 65%
“…Consistently, it was recently found that FACT mutant yeast demonstrated an increased level of H2Bub ( 78 ). The depletion of Ubp10, yeast counterpart of H2Bub deubiquitinase Usp7, activates cryptic transcription reporter in yeast strains with weak FACT mutation ( spt16–11 ) ( 78 ). Moreover, the severe FACT mutation alone leads to massive cryptic transcription ( 35–36 , 69 ), which is further enhanced in combination with Spt6 mutation ( 69 ).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The H2B fragment is cleaved from the intein and derivatized at its C-terminus using sodium 2-mercaptoethanesulfonate (MESNa); 2) a synthetic peptide encoding the Cterminal fragment of H2B bearing a thiazolidine-δ-mercaptolysine (δK) residue at the site of the isopeptide bond; and 3) full-length Ub (1-76) derivatized at its C-terminus with MES using a previously described chemoenzymatic approach that takes advantage of the ability of E1 Ub ligase to modify the C-terminus of Ub (El Oualid et al, 2010). Below, we first describe the expression and purification of each of the three peptide components, followed by a protocol to assemble H2B-Ub (Nune et al, 2018). While we used X. laevis histone sequences in this example, this protocol may be adapted for homologs from other organisms.…”
Section: Preparation Of Native H2b-ubmentioning
confidence: 99%
“…The Rtf1 subunit of Paf1C plays a key role in activating H2B K123ub through its histone modification domain (HMD), which directly contacts Rad6 (33,34,(41)(42)(43). In addition to Paf1C, the FACT histone chaperone complex has been implicated in regulating H2B K123ub as well as interacting with loci containing H2B K123ub (19,44). FACT is a conserved complex consisting of Spt16, Pob3, and Nhp6 in yeast and Spt16 and SSRP1 in humans (45).…”
Section: Introductionmentioning
confidence: 99%